2012
DOI: 10.1097/inf.0b013e31822fb15d
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Course and Short-term Outcomes of Term and Late Preterm Neonates Following Exposure to Prolonged Rupture of Membranes and/or Chorioamnionitis

Abstract: Our objective was to characterize the hospital course and short-term outcomes of neonates exposed to prolonged rupture of membranes (PROM), chorioamnionitis (CH), or both PROM and CH. Outcomes were positive blood culture and/or clinical signs of infection (+BC/CSI) prompting >4 days of antibiotics. Six neonates had a positive BC, 2 (0.6%) in the CH group and 4 (2.7%) in the PROM + CH group (P = 0.05); none of the neonates exposed to PROM alone had a +BC. These results support our current approach of withholdin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 10 publications
2
24
0
2
Order By: Relevance
“…Intrapartum antibiotic administration in the non-ACCA patients was not consistently reported. Notably, Jackson et al 18 (Fever) administered antibiotics to all neonates regardless of birth from ACCA or non-ACCA mothers. There does not appear to be a pattern of differential use of antibiotics which might bias the present analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Intrapartum antibiotic administration in the non-ACCA patients was not consistently reported. Notably, Jackson et al 18 (Fever) administered antibiotics to all neonates regardless of birth from ACCA or non-ACCA mothers. There does not appear to be a pattern of differential use of antibiotics which might bias the present analysis.…”
Section: Resultsmentioning
confidence: 99%
“…5 Jackson et al demonstrated that stable newborns with gestational age of at least 35 weeks and birth weight of at least 2,100 g, not requiring cardiorespiratory monitoring or respiratory support, could be admitted for intramuscular antibiotic treatment and monitoring to the normal newborn nursery and do not necessarily require transfer to a more intensive level of care. 18,[32][33][34] Neonatal antibiotics regime should be narrowed to target the specific pathogen once identified and should be discontinued when results of work-up for neonatal sepsis (e.g., negative C-reactive protein and/or serial blood cell counts) become available in culture negative neonates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparable data for EOS of all causes also reflect a reduction in attack rate, from 2.0 – 2.5 in the late 1980s and 1990s 2325 to 0.8 – 1.0 per 1000 live births since 2005 26, 27 . Among infants ≥ 34 28 or ≥ 35 29, 30 weeks gestation or with birth weights > 2500 g 26 , recent EOS rates are only 0.5 – 0.8 per 1000 live births. These much lower attack rates reflect a landscape that is fundamentally different from that extant when consensus guidelines for neonatal sepsis management were being developed 20 years ago.…”
Section: The Evolution Of Neonatal Sepsis Risk Assessmentmentioning
confidence: 99%
“…More recent reports indicate that the risk of EOS in infants born to women with chorioamnionitis is strongly dependent on gestational age. In three reports including 1892 infants born at ≥ 35 weeks’ gestation to mothers with clinical chorioamnionitis, the rates of EOS (positive blood culture at ≤ 72 hours of age) were only 0.47% 44 , 1.24% 29 , and 0.72% 30 (NNT to prevent one infection 80 – 210). In contrast, 4.8% to 16.9% 4549 of preterm infants exposed to chorioamnionitis develop EOS (NNT 6 – 21).…”
Section: The Evolution Of Neonatal Sepsis Risk Assessmentmentioning
confidence: 99%